FUNGSI PESANTREN SALAF DALAM MENYIKAPI KONTROVERSI AGAMA DAN POLITIK MELALUI PERSPEKTIF MODERASI BERAGAMA - Nashrul Fardhiansyah, Muhammad; Syani Amrulloh, Friendis (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Religious and political tensions in Indonesia have shown an increasing trend over the past decade, thereby demanding the role of religious institutions capable of functioning as conflict buffers. This article aims to critically analyze the function of pesantren in responding to religion–politics controversies through the perspective of religious moderation. The study employs a qualitative approach based on library research, utilizing content analysis techniques on authoritative works concerning religious moderation, pesantren, and religion–politics relations. The novelty of this research lies in the development of an integrative analytical framework that maps the function of pesantren not only within the educational sphere but also as a social mechanism for conflict buffering across three interconnected levels. The findings indicate that the effectiveness of pesantren as conflict buffers operates through: (1) the reproduction of inclusive religious reasoning rooted in the tradition of ikhtilaf within the study of classical Islamic texts (kitab kuning); (2) the mobilization of the kiai’s charismatic authority in social de-escalation practices; and (3) the institutionalization of political neutrality through internal pesantren regulations. These findings reinforce the argument that pesantren are key actors in the architecture of religious moderation in Indonesia, while also offering a conceptual model of pesantren functions as socio-religious stabilizers within a multicultural democratic context. The implications of this study highlight the importance of strengthening the epistemic and institutional capacities of pesantren in addressing contemporary religious and political contestations.